1999
DOI: 10.1038/sj.bmt.1701754
|View full text |Cite
|
Sign up to set email alerts
|

Organ toxicity and quality of life after allogeneic bone marrow transplantation in pediatric patients: a single centre retrospective analysis

Abstract: Summary:One hundred and fifty five pediatric patients underwent allogeneic bone marrow transplantation between 1980 and 1996 in the St Anna Children's Hospital in Vienna with an overall survival of 52.3% (81 patients). Seventythree patients with a minimum observation time of 1 year (1-13 years, median: 4.6) were analyzed retrospectively for chronic GVHD, organ toxicity (WHO score), growth and pubertal development. Chronic GVHD was diagnosed in 20 patients (27.3%), being extensive in 17 cases. Maximum organ tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 7 publications
2
42
4
Order By: Relevance
“…An important predictor of proxy-rated HRQoL was found in the child's demandingness perceived by the parents, assessed before and after admittance for SCT. The low post-SCT HRQoL ratings we found are in contrast with results reported in several other studies [6,15,28] in which an improved HRQoL was found after 6 months or more. One explanation for this difference could be the number of assessments done in some of these studies [15,34].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An important predictor of proxy-rated HRQoL was found in the child's demandingness perceived by the parents, assessed before and after admittance for SCT. The low post-SCT HRQoL ratings we found are in contrast with results reported in several other studies [6,15,28] in which an improved HRQoL was found after 6 months or more. One explanation for this difference could be the number of assessments done in some of these studies [15,34].…”
Section: Discussioncontrasting
confidence: 99%
“…Outcomes may vary from cure (and normality) to chronic graft-versushost disease (GVHD), relapse, or even death [6,15]. Many SCT survivors report long-term physical sequelae like fatigue [29], growth retardation and impaired pubertal development [5,28], pain [20,28], liver complications, and decreased lung functioning [38].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with previous studies on the long-term effects of having undergone BMT during childhood. 28,29,32 Where work-related functioning was concerned, our patients reported suffering from some illness-related impairment (e.g. working fewer hours per week because of illness-related complaints; only being able to do easy/ light chores due to illness-related impairment; only being able to work continuously for a short period of time or having to take regular breaks).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients (75%) reported no physical or psychological impairment. 29 Another cross-sectional study revealed that young adults who underwent BMT during childhood reported fewer problems when compared with their healthy peers with respect to interpersonal relationships, sleep, depression, and leisure possibilities, 3-9 years after BMT. 30 On the other hand, they reported more problems with regard to their physical appearance, and their studies and work possibilities.…”
mentioning
confidence: 99%